2018
DOI: 10.1007/s10803-018-3581-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characteristics of Autism Spectrum Disorder Among Spanish School-Age Children

Abstract: The present study aims to assess the prevalence of autism spectrum disorder (ASD) in preschool and school-age children following a two-phase procedure. The screening phase was performed on a sample of 5555 children taking into account parent and teacher information. The individual assessment included the ADI-R, ADOS-2 and Wechsler scales. The estimated prevalence was 1.55% in preschoolers and 1.00% in school-age children. Between 1.84 and 2.59% of the children exhibited subclinical diagnosis. The male-to-femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 61 publications
4
51
0
10
Order By: Relevance
“…Estimates report a prevalence of ASD of between 0.6% and 1.7% in children and adolescents, representing a serious public health problem. It has also been observed that males are up to 4 times more likely than females to be diagnosed with ASD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates report a prevalence of ASD of between 0.6% and 1.7% in children and adolescents, representing a serious public health problem. It has also been observed that males are up to 4 times more likely than females to be diagnosed with ASD [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a range of neurodevelopmental disorders characterized by impaired social communication and rigid repetitive patterns of behaviors or interests [American Psychiatric Association, 2013;Saqr, Braun, Porter, Barnette, & Hanks, 2018]. In recent decades, the worldwide prevalence of ASD has risen to 0.7-1.5% in childhood and adolescence [Morales-Hidalgo, Roige-Castellvi, Hernandez-Martinez, Voltas, & Canals, 2018], attracting the attention of researchers. Several resting-state functional magnetic resonance imaging (rsfMRI) studies of ASD have been published, especially with the emergence of data-sharing initiatives such as the Autism Brain Imaging Data Exchange (ABIDE) [Di Martino et al, 2017;Di Martino et al, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased awareness of the importance of early diagnosis and intervention for children with autism spectrum disorders (ASD), gold standard diagnostic measures, such as the Autism Diagnostic Observation Schedule [Lord et al, ] and Autism Diagnostic Observation Schedule‐2 (ADOS‐2 [Lord et al, ]), have become more accessible internationally for young children with ASD [Baird et al, ; Baron‐Cohen et al, ; Boilson, Staines, Ramirez, Posada, & Sweeney, ; Fombonne et al, ; Kim et al, ; Morales‐Hidalgo, Roigé‐Castellví, Hernández‐Martínez, Voltas, & Canals, ; Rudra et al, ; Sun, Allison, Matthews, et al, ]. The increased use of the ADOS‐G/ADOS‐2 in international studies has also been driven by the translation of the ADOS‐G/ADOS‐2 into more than 12 languages; however, studies examining the diagnostic validity of the measure have been mainly conducted in Western countries including the United States [Gotham, Risi, Pickles, & Lord, ], Canada [Risi et al, ], United Kingdom [Le Couteur, Haden, Hammal, & McConachie, ], the Netherlands [de Bildt et al, ], Germany [Bölte & Poustka, ], Poland [Chojnicka & Pisula, ], Greece [Papanikolaou et al, 2009], and Sweden [Zander, Sturm, & Bölte, ].…”
mentioning
confidence: 99%